To Search or to Ask: The Routing of Information Needs Between Traditional Search Engines and Social Networks - Oeldorf-Hirsch, Anne; Hecht, Brent; Morris, Meredith Ringel; Teevan, Jaime; Gergle, Darren (Proceedings of CSCW 2014, 2014)
In status message question asking (SMQA), members of social networking sites make use of status messages to express information needs to friends and contacts. We present findings from a laboratory study that examined 82 participants’ SMQA behaviors in the broader context of online information seeking. When given the option of using a search engine and/or a social network, we found that participants leveraged SMQA for 20% of their information needs, most often posing a question to their network in addition to issuing a query. We show the important roles played by the specificity of the information need and the perceived audience of a given network on routing decisions. We then demonstrate that information needs and routing decisions have varied effects on participants’ satisfaction, information value, and trust of outcomes. In addition to highlighting the complementary benefits and disadvantages of search and SMQA, our findings suggest that search engines can better address a proportion of people’s information needs by integrating SMQA capabilities into their systems.